Influence of gibberellic acid on tomato fructification - Blesa, Carlos; Gómez, Manuel (Ars Pharmaceutica (Internet), 1966)
One of the actions of gibberellic acid is to induce patenocarpia. However, its action depends on the state of floral development at the time of its application. Our trials in tomato plants show us that only fully parthenocarpic fruits are produced when the gibberellic acid is applied to newly opened flowers.When applied to closed flowers or that had been open for some time, partially ttenocárpicos fruits are obtained, being in the first case of greater intensity the action of gibberellic acid.Other facts are revealed: first, that the treatments with GA increase the size of the patients; and followed, which increases fruiting, especially when the treatments are done with flowers that were open long before the gibberellic acid was applied, due to a hearing action of natural fructation and von AG treatments